PERBEDAAN BERKUMUR – KUMUR LARUTAN TEH HIJAU DAN TEH HITAM TERHADAP PH SALIVA PADA SISWA KELAS IV DAN V DI SEKOLAH DASAR NEGERI JINGAH HABANG HILIR - Saparina, Saparina; Said, Fahmi; Sari, Emilda (JURNAL TERAPIS GIGI DAN MULUT, 2024)
The degree of salivation is one of the important factors that can affect the process of demineralization on the tooth surface. Under normal circumstances, the pH of saliva ranges from 6.8 to 7.2. This study aims to determine the difference between gargling green tea and black tea solutions on salivary pH. This type of research is a quasi-experimental research design with one group pretest posttest. The population is 26 people taking the sample using purposive sampling technique. The results of the data obtained will be analyzed using the Independent Sample T-Test test. The results of this study were the average pH of saliva before gargling with green tea solution was 6.9 and black tea solution was 7.3. Meanwhile, the average pH of saliva before gargling with green tea solution was 7.3 and black tea was 7. Based on the Independent Sample T-Test, the significance value was less than (0.005 0.05) so Ho was rejected. The conclusion of this study is that there is a difference between gargling green tea and black tea solutions on saliva pH in fourth and fifth grade students at SDN Jingah Habang Hilir. It is recommended that students take care of their health and besides that, the correct way of teeth and good gargling is expected with a green tea solution to prevent caries.